Pathology Informatics and Robotics Strategies for Improving Efficiency of COVID-19 Pooled Testing - Balaji Balasubramani BS; Kimberly J. Newsom PhD; Katherine A. Martinez BS; Petr Starostik MD; Michael Clare-Salzler MD; Srikar Chamala PhD (Elsevier, 2021)
The global rise of the coronavirus disease 2019 pandemic resulted in an exponentially increasing demand for severe acute respiratory syndrome coronavirus 2 testing, which resulted in shortage of reagents worldwide. This shortage has been further worsened by screening of asymptomatic populations such as returning employees, students, and so on, as part of plans to reopen the economy. To optimize the utilization of testing reagents and human resources, pool testing of populations with low prevalence has emerged as a promising strategy. Although pooling is an effective solution to reduce the number of reagents used for testing, the process of pooling samples together and tracking them throughout the entire workflow is challenging. To be effective, samples must be tracked into each pool, pool-tested and reported individually. In this article, we address these challenges using robotics and informatics.